Advection and removal of Pb-210 and stable Pb isotopes in the oceans: A general circulation model study - Henderson, G; Maier-Reimer, E (2002)
Natural Pb-isotope variability in the oceans encodes information about the sources of continental material to the oceans, about ocean circulation, and about Pb removal. In order to use this information, we must understand the natural cycle of Pb in the oceans, which is overprinted by large anthropogenic input. In this study we use 210Pb, which has not been significantly anthropogenically perturbed, to investigate oceanic Pb. GEOSECS 226Ra and model-derived atmospheric fluxes of 210Pb are used to input 210Pb into an ocean general circulation model. Irreversible scavenging of this 210Pb onto settling biogenic particles and at the seafloor are tuned so that the model replicates the observed pattern of 210Pb in the oceans. The best-fit model run provides a map of the variability of residence time for Pb. The global average residence time of Pb in this model is 48 yr, but there is over an order of magnitude variation between areas of high and low productivity. This is expected to enhance provinciality of Pb isotope ratios in the oceans. Because stable Pb isotopes are expected to behave in seawater in a similar fashion to 210Pb, the pattern of removal of 210Pb derived by the model can be used to investigate the behavior of stable Pb isotopes. We use a simplified input of Pb consisting of five point sources representing major rivers and a disseminated dust input. Although this simplified input scheme does not allow precise reconstruction of Pb concentration and isotopes in the oceans, it allows us to answer some first-order questions about the behavior of Pb as an ocean tracer. With a total Pb input of 6.3 × 107 mo1/yr (Chow T. J. and Patterson C. C., "The occurrence and significance of Pb isotopes in pelagic sediments," Geochim. Cosmochim. Acta 26, 263-308, 1962), the model predicts natural seawater Pb concentrations averaging 2.2 pmo1/kg. Even in the absence of anthropogenic input, the model ocean exhibits a near-surface maximum in Pb concentration. And the model suggests natural Pb concentrations in the Northern Hemisphere an order of magnitude higher than in the Southern Hemisphere. A point source of Pb is suggested to dominate the seawater Pb inventory close to the source but is reduced to typically less than 10% of the inventory by the time that Pb is advected out of the originating ocean. This length scale of advection for Pb isotope signals confirms their potential as tracers of ocean circulation. Assuming an 8% dissolution of dust, their input to the open ocean are seen to be a significant portion of Pb inventory throughout the oceans and make up >50% of the Pb inventory in the model's Southern Ocean. Finally, a preliminary investigation of the response of Pb-isotope distributions to changes in boundary conditions between glacial and interglacial times illustrates that significant variation in the Pb isotopes are expected in some regions, even for reasonably small changes in climate conditions. Copyright © 2002 Elsevier Science Ltd.